Efficacy/Safety of the Use of Glucocorticoids in Oral and Maxillofacial Surgery - Heilyn Joanna Nils; Cristina Arce Recatala; Antonio Castano; David Ribas; Javier Flores-Fraile (MDPI AG, 2023)
Introduction: Glucocorticoids, also known as corticosteroids or steroids, are drugs derived from cholesterol. They are synthesized by the adrenal cortex, along with other hormones, such as cortisol and aldosterone. Glucocorticoids are drugs recommended for patients undergoing surgery on the oral cavity, facial skeleton, and related cervical structures due to their high efficacy against inflammatory and immune processes. However, these drugs are restricted due to their multiple and serious adverse effects. The objective of this study was to verify the efficacy of corticosteroids administered in major surgeries of the oral cavity, as well as of the cervical and facial structures, based on the characteristics of the patient so as to select the best therapeutic strategy. Methods: Articles in the databases of PubMed, Nature Portfolio, Medline, Cochrane Library, and Google Scholar were thoroughly examined. Results: A total of 54 articles were selected to address the proposed objectives. The results obtained show that it is effective and safe to use glucocorticoids as pre- or postsurgical therapy in oral and maxillofacial surgery to control the processes of inflammation, pain, lockjaw, and edema. However, when referring to the use of these drugs, one must proceed with caution and pay particular attention when handling them. The concentration of the glucocorticoids used must be individualized, as well as the selection of the route of administration. Various studies show that, although the oral route is the most used route, the most effective route is the intramuscular route due to its easy absorption. However, for patients who have recurrent inflammatory and vesiculobullous ulcerative lesions, the topical route should be chosen to mitigate side effects, considering that recurrent applications must be made to prevent the worsening of the lesion and to avoid having to use medications enterally. In patients with cervicofacial infections, antibiotics continue to be the main drugs used to manage the condition in conjunction with corticosteroids. It is important to know the possible interactions of glucocorticoids with other medicines or food: it has been described that the interaction between Ritonavir, an antiretroviral drug that inhibits human immunodeficiency virus (HIV) proteases, and prednisone causes an increase in the concentration of prednisone, leading to possible toxicity in normally safe doses and, in many cases, iatrogenic Cushing's syndrome. It is also important to know the systemic or topical adverse effects of the chronic or high-dose use of glucocorticoids. Conclusions: It can be concluded that by making adequate use of glucocorticoid therapy in oral and maxillofacial surgery to manage clinical manifestations, it is possible to attenuate the morbidities of treatment and intervention.